Targeting Innate Immunity with dsRNA‐Conjugated Mesoporous Silica Nanoparticles Promotes Antitumor Effects on Breast Cancer Cells. Issue 5 (7th January 2016) - Ultimo, Amelia; Giménez, Cristina; Bartovsky, Pavel; Aznar, Elena; Sancenón, Félix; Marcos, M. Dolores; Amorós, Pedro; Bernardo, Ana R.; Martínez‐Máñez, Ramón; Jiménez‐Lara, Ana M.; Murguía, José R.
Abstract: We describe herein a Toll‐like receptor 3 (TLR3) targeting delivery system based on mesoporous silica nanoparticles capped with the synthetic double stranded RNA polyinosinic–polycytidylic acid (poly(I:C)) for controlled cargo delivery in SK‐BR‐3 breast carcinoma cells. Our results show that poly(I:C)‐conjugated nanoparticles efficiently targeted breast cancer cells due to dsRNA–TLR3 interaction. Such interaction also triggered apoptotic pathways in SK‐BR‐3, significantly decreasing cells viability. Poly(I:C) cytotoxic effect in breast carcinoma cells was enhanced by loading nanoparticles′ mesopores with the anthracyclinic antibiotic doxorubicin, a commonly used chemotherapeutic agent. Abstract : Messenger of death : A new drug‐delivery system based in mesoporous silica nanoparticles capped with the synthetic double stranded RNA polyinosinic–polycytidylic acid (poly(I:C)) for targeting breast carcinoma cells is reported (see figure).